The Effect of Red Pitaya Peel (Hylocereus polyrhizus Extract) on Malondialdehida Levels and Histopathology Profile in Diazinon Induced Rat (Rattus norvegicus) - Chanif Mahdi; Viski Fitri Hendrawan; Khoirus Viestaria (Indonesian Journal of Cancer Chemoprevention, 2019)
Diazinon, an organophosphate insecticide is widely used in agricultural sectors. The metabolic products of this organophosphate compound can increase Reactive Oxygen Species (ROS) in the body. It causes complications to the various organs, one of which is gastric. Red pitaya peel extract (Hylocereus polyrhizus) has high antioxidant activity in lowering ROS, in cases of diazinon poisoning. This study aims to determine the effectiveness of redpitaya peel extract in reducing the levels of Malondialdehyde (MDA) and repairing histopathological damage of rats induced by diazinon. This study used 20 tails of male white Wistar rats (Rattus norvegicus) from 8-12 weeks of age with the average weight of 150 grams . The subject was divided into 5 groups, which were negative control (-), positive control (+), treatment 1 (P1), treatment 2 (P2), and treatment 3 (P3). A dose of 40 mg/kg BW of Diazinon was given orally every day through feeding tube (sonde) for 5 consecutive days. Red pitaya peel extract was given to test groups with a dose of 150 mg/150 g BW, 200 mg/150 g BW and 250 mg/150 g BW, for 14 days. MDA levels were measured using the Thiobarbituric acid (TBA) test. Gastric histopathology features were stained with Hematoxylin-Eosin (HE) after 14 days. The MDA levels were analyzed quantitatively by ANOVA using SPSS version 22 for Windows and continued with honestly significant difference (HSD) test (α = 5%) and gastric histopathology were analyzed descriptively. The results showed that the extract of red pitaya peel with dose of 150 mg/150 g BW significantly (p<0.01) reduces MDA level in gastric dan improves the histopathology of the gastric. Red pitaya peel extract at a dose of 150 mg/150 g BW was able to significantly decrease MDA levels and improve the histopathology feature of the gastric in white rats induced by diazinon. So this can be summarised that giving red pitaya extract in rats have a very significant effect on the level of malondialdehyde production and it could repair rats stomach tissue that induced by diazinon.Keywords: diazinon, histopathology, MDA, red pitaya peel